Development of alginate-based hydrogels/cryogels by gelation under pressure - Barros, Alexandre António Antunes (2014)
Published in "Journal of tissue engineering and regenerative medicine, vol. 8, s1 (June 2014)". Special Issue: Tissue Engineering & Regenerative Medicine International Society, European Chapter Meeting, 10–13 June, 2014, Genova, Italy